O efeito do endosso de celebridade na negligência da omissão nos diferentes níveis de ceticismo - Silva, Jussara Goulart da (2018)
The purpose of this thesis was to identify the effect of celebrity endorsement on omission neglect at different levels of skepticism. The omission neglect is understood as the lack of understanding of the consumer due to information lacking in the decision-making processes of purchase. The purpose was to manipulate the number of attributes of an object as well as the endorsement of a celebrity, in the three experiments completed simultaneously. The data acquired from the sample, composed of 512 university students from a public higher education institution, were compiled and analyzed through analysis of variance. The analysis of the three experiments concluded: a) in advertising endorsed by a celebrity, both the non-expert consumers and the experts neglected the missing information and made positive evaluations about the endorsed product; b) in an advertisement with celebrity endorsement of high congruence with the product offered, both non-experts and experts evaluated the object in the same way, regardless of the quantity of positive attributes available, and c) in an advertisement scenario in which the degree was also measured of individual skepticism, participants recognized the neglect of omission in the process of object evaluation.